Public service delivery - role of Union Digital Center (UDC) and impact on improving governance and development : a case study of Narayanganj District, Bangladesh - Saleheen, Saroar Ahmed (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of MA in Governance and Development, 2015.